Association Between Hypertensive Disorders of Pregnancy and Later Risk of Cardiomyopathy. Issue 4 (December 2016) - Behrens, Ida; Basit, Saima; Lykke, Jacob Alexander; Ranthe, Mattis Flyvholm; Wohlfahrt, Jan; Bundgaard, Henning; Melbye, Mads; Boyd, Heather A.
Abstract : ( JAMA 2016;315(10):1026–1033) Hypertensive disorders of pregnancy (HDP), including preeclampsia and gestational hypertension, are common, occurring in approximately 10% of parturients worldwide. Women with preeclampsia have been shown to be at increased risk for peripartum cardiomyopathy as well as cardiovascular disease later in life. It has not yet been determined if these women are also at greater risk for developing cardiomyopathy beyond the peripartum period. However, recent research has suggested women with preeclampsia may undergo some degree of cardiac remodeling that results in persistent cardiac dysfunction. The aim of this study was to investigate the association between HDP and cardiomyopathy after the peripartum period.